1985
DOI: 10.1111/j.1471-6402.1985.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Correlates of Age and Life Roles in Adult Women

Abstract: The association between age/family stage, career role, and personality traits was studied using a multivariate statistical approach. Young adult, midlife, and older women from four role groups-homemaker, married career, single career, and student-were compared on a number of personality measures including achievement motivation, affiliation, autonomy, cultural sex role characteristics, self esteem, and adjustment.While some of the expected group differences did not appear, some significant age and role differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Many of the studies reviewed above focus exclusively on women and have not included men (e.g., Erdwins et al 1983;Helson and Moane 1987;Kasen et al 2006;Mellinger and Erdwins 1985;Roberts et al 2002). Consequently, relatively less is known regarding agerelated differences in men's masculine and feminine traits.…”
Section: Masculine and Feminine Traitsmentioning
confidence: 94%
See 2 more Smart Citations
“…Many of the studies reviewed above focus exclusively on women and have not included men (e.g., Erdwins et al 1983;Helson and Moane 1987;Kasen et al 2006;Mellinger and Erdwins 1985;Roberts et al 2002). Consequently, relatively less is known regarding agerelated differences in men's masculine and feminine traits.…”
Section: Masculine and Feminine Traitsmentioning
confidence: 94%
“…Support for this hypothesis can be found when previous cross-sectional comparisons of women are examined. Older women's masculine personality trait scores are lower than those of younger women (Erdwins et al 1983;Mellinger and Erdwins 1985). In these studies, it is unclear whether there is heterogeneity among subgroups of older women because women 60 and older have been examined as a single demographic group.…”
Section: Masculine and Feminine Traitsmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, internal locus of control is associated with lower levels of anxiety and depression, and higher levels of self-esteem and life satisfaction . Previous research has shown that, in general, individuals employed in supervisory and management positions score higher on internal locus of control than those working in non-supervisory positions (Kapalka and Lachenmeyer, 1988;Mellinger and Erdwins, 1985;St-Yves et al, 1989). Thus, it may be anticipated that unemployed managers will perceive relatively higher degrees of personal control and, as a result, will be more intrinsically motivated in their job search, although they may verbalize external causes to explain or defend themselves against actual or expected failures during job search (Rotter, 1966).…”
Section: Personal Controlmentioning
confidence: 99%
“…A woman who is both married and a student may have many demands on her time and emotions and little left to invest in the mother-daughter relationship. Or, as shown by Mellinger and Erdwins (1985), she may feel less constricted by familial obligations. Perhaps the transition to the parental role heralds a positive change in mother-daughter interdependence; that is, marital role convergence is a negative influence whereas parental role convergence may be a positive influence.…”
Section: -05mentioning
confidence: 99%